2021
DOI: 10.1021/acssuschemeng.1c01513
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol as a Liquid Organic Hydrogen Carrier for Seasonal Microgrid Application: Catalysis, Theory, and Engineering Feasibility

Abstract: In this work, we describe the benefits and challenges of a green approach to seasonal energy storage using ethanol as a liquid organic hydrogen carrier (LOHC). We evaluate the cycling efficiency of hydrogen release from ethanol (EtOH) to form ethyl acetate (EtOAc) as the spent LOHC and the subsequent regeneration of EtOH from EtOAc catalyzed by a single molecular catalyst, Ru-MACHO, at a moderate pressure of H 2 , mild reaction temperature, and high selectivity. From experimental and computational studies, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…6−10 In contrast, the hydrogenation of the aromatic −C�C− double bond is primarily confined to heterogeneous catalysts at higher temperatures and H 2 pressures, 11 which can limit the coupling of existing electrolyzer technology to provide suitable H 2 pressure. Extending beyond the aforementioned oxygenates, our studies on ethanol 12 suggest a closer, systematic examination of 1,4-butanediol (BDO) 13,14 as an LOHC candidate. BDO undergoes similar chemical transformations to that of ethanol with similar thermodynamic considerations along with high conversion and high product selectivity (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…6−10 In contrast, the hydrogenation of the aromatic −C�C− double bond is primarily confined to heterogeneous catalysts at higher temperatures and H 2 pressures, 11 which can limit the coupling of existing electrolyzer technology to provide suitable H 2 pressure. Extending beyond the aforementioned oxygenates, our studies on ethanol 12 suggest a closer, systematic examination of 1,4-butanediol (BDO) 13,14 as an LOHC candidate. BDO undergoes similar chemical transformations to that of ethanol with similar thermodynamic considerations along with high conversion and high product selectivity (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 95%
“…Extending beyond the aforementioned oxygenates, our studies on ethanol suggest a closer, systematic examination of 1,4-butanediol (BDO) , as an LOHC candidate. BDO undergoes similar chemical transformations to that of ethanol with similar thermodynamic considerations along with high conversion and high product selectivity (Scheme ).…”
Section: Introductionmentioning
confidence: 96%
“…TMCs are oen used as bio-inspired homogeneous catalysts which account for over 15% of all industrial catalytic processes and enable key catalytic transformations such as for pharmaceuticals, ne chemicals, and energy applications. [25][26][27][28][29][30][31][32] Recent studies have revealed the promise of data-driven quantum chemical methods to understand structure-function relations in TMCs. [33][34][35][36][37][38] Availability of structure-property data from QM calculations and/or experiments is central to the success of data-driven chemical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, an analysis of the DHC of ethanol to produce hydrogen and ethyl acetate was performed in the liquid phase using a homogeneous catalyst. [ 9 ] A challenge identified in this study was a poor overall energy efficiency, which arose from the high heating and cooling requirements associated with the reflux of ethanol and ethyl acetate. To address this, the current work presents a thermodynamic analysis of the ethanol–ethyl acetate storage cycle in the gas phase where reflux can be avoided.…”
Section: Introductionmentioning
confidence: 99%